A critical review on surface modifications mitigating dairy fouling. Issue 5 (11th July 2021) - Saget, Manon; de Almeida, Caroline Françolle; Fierro, Vanessa; Celzard, Alain; Delaplace, Guillaume; Thomy, Vincent; Coffinier, Yannick; Jimenez, Maude
Abstract: Thermal treatments performed in food processing industries generate fouling. This fouling deposit impairs heat transfer mechanism by creating a thermal resistance, thus leading to regular shutdown of the processes. Therefore, periodic and harsh cleaning‐in‐place (CIP) procedures are implemented. This CIP involves the use of chemicals and high amounts of water, thus increasing environmental burden. It has been estimated that 80% of production costs are owed to dairy fouling deposit. Since the 1970s, different types of surface modifications have been performed either to prevent fouling deposition (anti‐fouling) or to facilitate removal (fouling‐release). This review points out the impacts of surface modification on type A dairy fouling and on cleaning behaviors under batch and continuous flow conditions. Both types of anti‐fouling and fouling‐release coatings are reported as well as the different techniques used to modify stainless steel surface. Finally, methods for testing and characterising the effectiveness of coatings in mitigating dairy fouling are discussed.